The prevalence, characteristics, associated comorbidities and medical management of patients with atrial fibrillation in a tertiary setting in the Western Cape - Potgieter, S; Doubell, AF; Germishuys, C; Moses, J (SA Heart Journal, 2025)
Introduction: The prevalence of atrial fibrillation (AF) in high-income countries is high, with less known about low- to middle-income countries. Information on the patient profile and application of adequate guideline-directed management in this low-middle income setting is lacking. This study aimed to determine the prevalence, clinical profile and management of patients with AF across all disciplines in a tertiary setting, and to compare the management of these patients with current guidelines. Methods: Electrocardiograms (n = 13 414) recorded at Tygerberg Hospital for patients > 18 years between 1 July 2018 – 30 June 2019 were screened and medical records reviewed. Results: An AF prevalence of 3.4% (n = 460) was found, which corresponded to 341 patients and 238 complete medical records. The mean age was 65.4 (±13.9) years and the most prevalent comorbidities reported were hypertension (63.9%, n = 152) and diabetes mellitus (21%, n = 46). Valvular heart disease was found in 31.1% (n = 74). In 80.7% (n = 192) of patients anticoagulation was indicated; however, only 65.1% (n = 125) of those indicated received it, mostly with warfarin. Time in therapeutic range (TTR) was poor (26.5%). Rate control (< 110 bpm), was seen on 80.9% (n = 372) of ECGs and beta blockers were most frequently used for rate control (65.1%, n = 155). No patients had documented information indicating that they received medical or interventional rhythm control management. Discussion: The AF prevalence and patient profile resemble those of patients in high-income countries. Slightly more than half of patients qualifying for anticoagulation received this with warfarin, with suboptimal TTR. Rate control strategies were somewhat reassuring; however, the lack of early rhythm control may be disadvantageous to our patients.